Documentary Video Introduction of Modern Tebe System Based on Video in Cemenggaon Village, Sukawati, Gianyar - Palguna Brahmanta, I Wayan Agus; Surya Dinata, Ramanda Dimas; Pradnyanita, Anak Agung Sagung Intan (Malikussaleh University, Aceh, Indonesia, 2025)
Cemenggaon traditional village, located in Sukawati Gianyar subdistrict, has developed a modern tebe system to deal with the problem of organic waste. This modern tebe has been implemented in every resident's house, with around 245 heads of families already having at least two modern tebe. Cooperation between the government, stakeholders, and others is needed to manage non-organic waste. Also, residents, where several waste banks and non-organic waste have been prepared, will be sorted and have a sale value. Introducing the modern tebe system to the broader community, especially the younger generation, will train a responsible attitude towards preserving nature by caring for and keeping the environment clean of rubbish. Some respondents do not know and do not have sufficient insight into organic waste management, nor do they know how to handle organic waste using the modern tebe system.